2020
DOI: 10.1111/jrh.12414
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Posttreatment Patient‐Provider Communication and Follow‐Up Care Among Self‐Identified Rural Cancer Survivors in Illinois

Abstract: Purpose As disparities in rural‐urban cancer survivorship rates continue to widen, optimizing patient‐provider communication regarding timely follow‐up care is a potential mechanism to improving survivorship‐related outcomes. The current study examines sociodemographic and health predictors of posttreatment patient‐provider communication and follow‐up care and associations between written communication and timely follow‐up care for cancer survivors who identify as rural. Methods Data were analyzed from posttre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…There is increasing research and practice-level attention on survivorship care communication, partly due to the mixed ndings on the utility of survivorship care plans and their association with improved survivorship outcomes. [24,41,42] Lewis-Thames et al, [43] investigated patient-provider survivorship care communication with rural active and posttreatment survivors. Therein, less than half of the survivors received "in detail" communication about late or long-term side effects of cancer treatment (32%) and emotional or social needs related to cancer and lifestyle or health recommendations such as diet (47%).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing research and practice-level attention on survivorship care communication, partly due to the mixed ndings on the utility of survivorship care plans and their association with improved survivorship outcomes. [24,41,42] Lewis-Thames et al, [43] investigated patient-provider survivorship care communication with rural active and posttreatment survivors. Therein, less than half of the survivors received "in detail" communication about late or long-term side effects of cancer treatment (32%) and emotional or social needs related to cancer and lifestyle or health recommendations such as diet (47%).…”
Section: Discussionmentioning
confidence: 99%
“…In a survey study of rural cancer survivors, Lewis-Thames and colleagues found that rural survivors receiving written post-treatment survivorship communication had greater odds of reporting timely follow-up care [33]. In an evaluation of a structured care plan called Care Sequence in five safety-net institutions and five non-safety-net institutions, the SCP was perceived as useful [26].…”
Section: Theme 1: Benefits Of Survivorship Care Plansmentioning
confidence: 99%
“…Reduced care access contributes to disparities in outcomes, as rural cancer centers often have fewer resources, personnel, specialists, and treatment options available 5,26–28 . Thus, considering the unique challenges facing care providers and patients in rural settings, and as a contributor to the contextual rural patient experience, patient‐provider communication may be a mechanism to improve outcomes and well‐being of patients 29,30 …”
Section: Introductionmentioning
confidence: 99%
“…5,[26][27][28] Thus, considering the unique challenges facing care providers and patients in rural settings, and as a contributor to the contextual rural patient experience, patient-provider communication may be a mechanism to improve outcomes and well-being of patients. 29,30 Given both the documented linkages between financial toxicity and psychosocial outcomes and the need to better understand the rural cancer patient experience, the current study examined the relationship between financial toxicity, health care team communication, and psychosocial well-being among rural cancer patients and survivors. Our first aim was to document associations between financial toxicity and psychosocial well-being among rural adults with cancer.…”
Section: Introductionmentioning
confidence: 99%